The Infliximab Multinational Psoriatic Arthritis Controlled Trial (IMPACT): results of radiographic analyses after 1 year. Issue 8 (26th January 2006) - Kavanaugh, A; Antoni, C E; Gladman, D; Wassenberg, S; Zhou, B; Beutler, A; Keenan, G; Burmester, G; Furst, D E; Weisman, M H; Kalden, J R; Smolen, J; et al.
Abstract : Objective: Infliximab is effective in improving signs and symptoms of joint/skin involvement, functional status, and quality of life in patients with psoriatic arthritis (PsA). Using IMPACT trial data, we assessed the effect of infliximab (IFX) on structural damage in PsA. Methods: Patients with active PsA were randomly assigned to receive placebo (PBO/IFX) or infliximab 5 mg/kg (IFX/IFX) at weeks 0, 2, 6, and 14, with the primary endpoint at week 16. The PBO group received infliximab loading doses at weeks 16, 18, and 22. Thereafter, all patients received infliximab 5 mg/kg every 8 weeks through week 50. Hand/feet radiographs were obtained at weeks 0 and 50. Total radiographic scores were determined using the PsA modified van der Heijde-Sharp (vdH-S) score. Projected annual rate of progression was calculated by dividing x ray score by disease duration (years). Results: As reported previously, 65% of infliximab treated patients versus 10% of PBO treated patients achieved an ACR20 response at week 16 (p<0.001). At week 50, 69% of patients achieved an ACR20 response. Radiographs (baseline and week 50) were available for 72/104 patients. At baseline, estimated mean annual rate of progression was 5.8 modified vdH-S points/year. Mean (median) changes from baseline to week 50 in the total modified vdH-S score were −1.95 (−0.50) for PBO/IFX and −1.52 (−0.50) for IFX/IFX patients (p = NS). At week 50, 85% and 84% of patients in the PBO/IFX and IFX/IFX groups had no worsening in the total modified vdH-S score. Conclusion: Infliximab inhibits radiographic progression in patients with PsA through week 50.